Comprehensive evaluation of the optimal rates of irrigation and potassium application for strawberry - Yang, Xiaoqing; Du, Rongcheng; Zhang, Mengchi; Feng, Huawei; Wang, Ziqing; Zhang, Zhi (International Journal of Agricultural and Biological Engineering, 2023)
Accurate and effective management of irrigation and fertilization is essential for efficient greenhouse strawberry production. Here, the effects of the combined application of water and potassium on strawberry growth were evaluated by experimenting with 12 treatments, including four transpiration (ETC)-based irrigation levels (W1: 100% ETC, W2: 85% ETC, W3: 70% ETC, and W4: 55% ETC) and three potassium levels according to the target yield (K1: 369.5 kg/hm2, K2: 307.9 kg/hm2, and K3: 246.3 kg/hm2). Various indexes of strawberry yield, fruit quality, water and fertilizer utilization efficiency, and soil nutrient residues were measured. Irrigation and potassium application had significant effects on strawberry production. Higher irrigation levels increased yield (Y), and moderate water and potassium application increased single fruit weight (SFW), water utilization efficiency (WUE), total soluble sugar (TSSC), and the sugar-acid ratio (SAR). While low-application of potassium increased the soluble protein content (SP), partial factor productivity of potassium (PFPK), and reduce nutrient residues in soil effectively. A comprehensive system for evaluating strawberry growth and its benefits to the soil environment was developed. The FAHP and CRITIC methods were used to calculate the subjective weight and objective weight of each index, respectively. The largest subjective weight was observed for Y (0.200), and the largest objective weight was observed for soil-available potassium (0.101). The final weight was determined using Game theory; Y had the highest weight (0.185), and free amino acids (FAA) had the lowest weight (0.047). Grey relational analysis (GRA) was used to evaluate the optimal irrigation and potassium scheme for accomplishing multiple objectives. The response of the comprehensive score of strawberries to irrigation and potassium exhibited a negative parabolic relationship, and the effect of irrigation was greater than the effect of potassium application. There was a significant interaction between irrigation and potassium application, and an irrigation amount of 2053-2525 m3/hm2 with a potassium application rate of 288.1-334.2 kg/hm2 was optimal for promoting strawberry yield, fruit quality, and efficiency and reducing soil nutrient residues. The results of this study provide new insights that could aid the development of sustainable approaches for enhancing agricultural production.Keywords: strawberry, irrigation, potassium, FAHP, CRITIC, nutrient residuesDOI: 10.25165/j.ijabe.20231602.7591Citation: Yang X Q, Du R C, Zhang M C, Feng H W, Wang Z Q, Zhang Z. Comprehensive evaluation of the optimal rates of irrigation and potassium application for strawberry. Int J Agric & Biol Eng, 2023; 16(2): 65-72.